(untitled) (Research, Society and Development, 2020)
To analyze the speed and amplitude of mandibular movements during speech before and after lingual frenectomy. Comparative, descriptive and cross-sectional study. Sample composed of 10 subjects with lingual frenulum alteration, between 15 and 21 years old. This study was started in October 2018 and ended in July 2019. Patients were taken to apply the Lingual Frenulum Evaluation Protocol, followed by measuring the maximum mouth opening with caliper; of mouth opening and closing speed and the range of mandibular movements during speech with a BioEGN electrognathograph. After 30 days, new records were obtained. Data were analyzed using the IMB SPSS version 23 statistical software. When comparing the subjects’ mandibular movements before and after lingual frenectomy, the analysis of the variables showed that they presented statistically significant difference in the movements during the speech of Frontal Vertical Vertical Amplitude (AVPF). ) and Closing Speed ​​(FV), as well as the variables Maximum Mouth Opening (AMB) and Maximum Mouth Opening with tongue touching the incisive papilla (AMBpi), conferring ankyloglossia interference on the performance of mandibular movements. The present study shows that the speed and amplitude of mandibular movements during speech were improved after lingual frenectomy in patients with ankyloglossia.